Misconception Analysis of the Upin and Ipin Movie in Biology Learning on Viruses, Ecosystems, and Environmental Pollution Material - Fitria Amalia; Hanum Mukti Rahayu; Mahwar Qurbaniah (Bioedukasi: Jurnal Pendidikan Biologi, 2023)
Misconceptions often occur in education, especially in biology.  Misconceptions can occur outside of school. In addition, there are preconceptions of other sources.  Sources of these preconceptions are, for example, films with unorganized science-fiction themes. Film  The most popular children's animation in the community today is Upin & Ipin. Study  This study aims to find out the misconceptions in the Upin & Ipin film with the theme  learning biology material on viruses, ecosystems, and environmental pollution. Which method  used in this research is descriptive method with qualitative data approach. Technique  data collection uses observation and documentation while data collection tools  in the form of observation sheets and documentation tools in the form of video files for the film Upin & Ipin season 11 with the Erase Virus 1-3, Season 10 with the title Ecosystem part 1-3, Season 7 with the title Dangers of Jerebu part 1-3. The results of the analysis of misconceptions of the film Upin & Ipin are the most in episodes  the Erase Virus. There are 5 concepts that experience misconceptions with the category of misidentification by 71.42% with high level category and there are 2 concepts with category  oversimplification of 28.57% in the low level category. For Upin & Ipin film episode Ecosystem and Dangers of Jerebu there are 9 concepts but there are no misconceptions. Based on  From this research, it can be concluded that there are misconceptions in Upin & Ipin film season 11 episodes the Erase Virus part 1-3.